SME Upgrading Programs : Exploring Initiatives that Combine Market Linkages and Capability Strengthening - World Bank (World Bank, Washington, DC, 2020)
A key focus of most countries is to stimulate growth in their small and medium enterprises (SME) population. There are various influences on SME competitiveness. Governments, development partners, non-profit entities, and private sector associations and firms intervene to aim to increase SME competitiveness by addressing market, coordination, and government failures that impact on these four areas. This paper examines interventions that seek to address firm-level capabilities and access to markets in some type of integrated fashion. A substantial body of SME interventions aim to address both capabilities and markets. The aim of this paper is to provide practical information to World Bank Group (WBG) task team leaders and other development practitioners on the design and implementation of SME support initiatives that incorporate an SME upgrading and market development element. It is structured as follows: section II describes the approach taken to identify relevant interventions; section III presents findings on types of interventions; section IV presents detailed case studies on four interventions; section V presents findings from the case studies and emerging practices within WBG, and section VI concludes with lessons learned and recommendations for WBG teams. A long list of programs is presented in Annex 1, and a literature review is presented in Annex 2.